2018
DOI: 10.1016/j.ebiom.2018.06.017
|View full text |Cite
|
Sign up to set email alerts
|

Gefitinib and Methotrexate to Treat Ectopic Pregnancies with a Pre-Treatment Serum hCG 1000–10,000 IU/L: Phase II Open Label, Single Arm Multi-Centre Trial

Abstract: BackgroundEctopic pregnancies are a leading cause of maternal mortality. Most are treated surgically. We evaluated the efficacy and safety of combining oral gefitinib (epidermal growth factor receptor inhibitor) with methotrexate to treat larger ectopic pregnancies.MethodsWe performed a phase II, single arm, open label study across four hospitals in Edinburgh and Melbourne. We recruited women with a stable tubal ectopic pregnancy and a pre-treatment serum hCG between 1000 and 10,000 IU/L. We administered intra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 12 publications
0
10
1
Order By: Relevance
“…To date, early human trials of combination gefitinib and methotrexate to treat nontubal ectopic pregnancy have been promising . However, the pretreatment and peak hCG of these interstitial ectopic cases were lower than our patient and only one had fetal cardiac activity.…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…To date, early human trials of combination gefitinib and methotrexate to treat nontubal ectopic pregnancy have been promising . However, the pretreatment and peak hCG of these interstitial ectopic cases were lower than our patient and only one had fetal cardiac activity.…”
Section: Discussioncontrasting
confidence: 70%
“…During the early phase I trial, combination gefitinib and methotrexate showed a 34% reduction in median resolution time compared to methotrexate therapy alone for tubal ectopic pregnancies . Additionally, during the phase II study, an 86% success rate was found for tubal ectopic pregnancies with a pretreatment hCG between 1000 and 10 000 IU/L . Furthermore, a case series of eight women with nontubal ectopic pregnancies and pretreatment hCG between 2485 and 48 550 IU/L showed successful treatment with combination gefitinib and methotrexate without surgical intervention .…”
Section: Introductionmentioning
confidence: 98%
“…Cervical pregnancy responded to multiple dose methotrexate and gefitinib 250 mg twice daily for 5 days. 18,19 Among surgically managed patients, 18 patients were emergency and 25 cases of elective surgery. 13 patients were ruptured ectopic and 25 cases unruptured.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the sample size was estimated as 30 individuals considering α = 0.05, β = 0.1, and d = 1 and using the formula n = 2 (Z_(α/2) Z_β) ^ 2/d ^ 2. Given the sample loss of 20%, 35 samples were considered in this study (26).…”
Section: Discussionmentioning
confidence: 99%